(untitled) (Biodiversitas Journal of Biological Diversity, 2018)
Fathin AN, Ratnaningrum YWN. 2018. The differences in floral structures of three sandalwood variants in one of Gunung Sewu (Indonesia) population, and their consequences on visitor diversity and visitation rate. Biodiversitas 19: 1097-1101. Sandalwood, one of the most economically valuable endangered species, is native to the southeastern Indonesian islands, but it has recently occurred as new landraces in Gunung Sewu, Java island. Our previous findings found three floral variants (YBF, refers to “yellow big flower”; RBF, “red big flower”; and RSF, “red small flower”, respectively) of sandalwood landraces in Gunung Sewu. The differences in floral structures among variants were also reported. In this study, we further analyzed these variant differences and their consequences on visitor diversity and visitation rate in the Bleberan population, one of the most genetically diverse populations in Gunung Sewu Geopark, in the 2016 flowering period. Floral visitor diversity, visitation rate, and pollination behavior were observed in each floral variant. Visitor preference to a certain variant might be attributed to the differences in floral color and size. YBF was visited more by coleopterans and hemipterans, while both RBF and RSF were visited more by hymenopterans. The dipterans and lepidopterans visited both yellow and red flowers at a similar rate. The bigger flowers of RBF and YBF received more visits than RSF.